Optical bifurcations in media with the Kerr nonlinearity - Zegadlo, Krzysztof; Karpierz, Miroslaw (Photonics Letters of Poland, 2013)
Spontaneous symmetry breaking phenomenon or optical bifurcation occurs in media with some kind of symmetry when self-focusing nonlinearity is applied. In this manuscript that effect is investigated for the Kerr nonlinearity in structures with periodical distribution of refractive index. Not only symmetry bifurcation of the fundamental mode but also properties of a beam propagating in such structures has been studied. Spontaneous symmetry breaking has been presented both as a function of total beam power and as a function of relative refractive index change. The results can be utilized for all optical switching effect. Full Text: PDF References D. Landau, E.M. Lifshitz, Quantum Mechanics (Moscow, Nauka 1974). Y.S. Kivshar, and G.P. Agrawal, Optical Solitons: From Fibers to Photonic Crystals (New York, Academic 2003). S. Giorgini, L.P. Pitaevskii, and S. Stringari, "Theory of ultracold atomic Fermi gases", Rev. Mod. Phys. 80, 1215 (2008). CrossRef E.A. Ostrovskaya, Y.S. Kivshar, M. Lisak, B. Hall, F. Cattani, and D. Anderson, "Coupled-mode theory for Bose-Einstein condensates", Phys. Rev. A 61, 031601 (2000). CrossRef M. Albiez, R. Gati, J. Folling, S. Hunsmann, M. Cristiani, and M.K. Oberthaler, "Direct Observation of Tunneling and Nonlinear Self-Trapping in a Single Bosonic Josephson Junction", Phys. Rev. Lett. 95, 010402 (2005). CrossRef P.G. Kevrekidis, Z. Chen, B.A. Malomed, D.J. Frantzeskakis, and M.I. Weinstein, "Spontaneous symmetry breaking in photonic lattices: Theory and experiment", Phys. Lett. A 340, 275 (2005). CrossRef S.M. Jensen, "The nonlinear coherent coupler", IEEE J. Quantum Electron. QE-18, 1580 (1982). CrossRef M.A. Karpierz, "Nonlinear directional couplers with asymmetrical distribution of nonlinearity", Opt. Commun. 90, 241 (1992). CrossRef A.W. Snyder, D.J. Mitchell, L. Poladian, D.R. Rowland, and Y. Chen, "Physics of nonlinear fiber couplers", J. Opt. Soc. Am. B 8, 2102 (1991). CrossRef C. Pare and M. Florjańczyk, "Approximate model of soliton dynamics in all-optical couplers", Phys. Rev. A 41, 6287 (1990). CrossRef W.C.K. Mak, B.A. Malomed, and P.L. Chu, "Solitary waves in coupled nonlinear waveguides with Bragg gratings", J. Opt. Soc. Am. B 15, 1685 (1998). CrossRef G. Herring, P.G. Kevrekidis, B.A. Malomed, R. Carretero-Gonzalez, and D.J. Frantzeskakis, "Symmetry breaking in linearly coupled dynamical lattices", Phys. Rev. E 76, 066606 (2007). CrossRef Lj. Hadzievski, G. Gligoric, A. Maluckov, and B.A. Malomed, "Interface solitons in one-dimensional locally coupled lattice systems", Phys. Rev. A 82, 033806 (2010) CrossRef V.A. Brazhnyi and B.A. Malomed, "Spontaneous symmetry breaking in Schrödinger lattices with two nonlinear sites", Phys. Rev. A 83, 053844 (2011). CrossRef K.A. Brzdąkiewicz, M.A. Karpierz, A. Fratalocchi, G. Assanto, "Nematic liquid crystal waveguide arrays", Opto-electron. Rev. 13, 107 (2005) DirectLink J.E. Midwinter, Optical Fibers for transmission (London, John Wiley 1979) J. Van Roey, J. van der Donk, and P.E. Lagasse, "Beam-propagation method: analysis and assessment", J. Opt. Soc. Am. 71, 803 (1981) CrossRef Y. Chung and N. Dagli, J. Quantum. Electron. 26, 1335 (1990) CrossRef D. Yevick, "A guide to electric field propagation techniques for guided-wave optics", Opt. Quant. Electron. 26, 185 (1994) CrossRef C. Ma and E. Van Keuren, "A three-dimensional wide-angle BPM for optical waveguide structures", Opt. Express 15, 402 (2007) CrossRef F.A. Sala and M.A. Karpierz, "Modeling of molecular reorientation and beam propagation in chiral and non-chiral nematic liquid crystals", Opt. Express 20, 13923 (2012) CrossRef P.S. Jung and M.A. Karpierz, Opt. Commun. 285, 4184 (2012) CrossRef P.S. Jung and M.A. Karpierz, "Analysis of Light Propagation in Optical Fibers with a High Step Index", Acta Phys. Polon. A 122, 829 (2012). CrossRef S. Jungling, "A study and optimization of eigenmode calculations using the imaginary-distance beam-propagation method", IEEE J. Quantum Elect. 30, 2098 (1994) CrossRef C.L. Xu, W.P. Huang, and S.K. Chaudhuri, "Efficient and accurate vector mode calculations by beam propagation method", J. Lightwave Technol. 11, 1209 (1993) CrossRef Y.Z. He and F.G. Shi, "Finite-difference imaginary-distance beam propagation method for modeling of the fundamental mode of photonic crystal fibers", Opt. Commun. 225, 151 (2003) CrossRef